2014
DOI: 10.1016/j.csbj.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics and population structure of Entamoeba histolytica

Abstract: Amoebiasis caused by the gastrointestinal parasite Entamoeba histolytica has diverse disease outcomes. Study of genome and evolution of this fascinating parasite will help us to understand the basis of its virulence and explain why, when and how it causes diseases. In this review, we have summarized current knowledge regarding evolutionary genomics of E. histolytica and discussed their association with parasite phenotypes and its differential pathogenic behavior. How genetic diversity reveals parasite populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…These data agree well with the phylogenetic position of these Entamoeba species in previous reports (Clark et al. ; Das and Ganguly ; Tachibana et al. ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These data agree well with the phylogenetic position of these Entamoeba species in previous reports (Clark et al. ; Das and Ganguly ; Tachibana et al. ).…”
Section: Resultssupporting
confidence: 93%
“…), but is phylogenetically distant from E. histolytica in the genus Entamoeba (Clark et al. ; Das and Ganguly ). Therefore, transplant from E. histolytica to E. invadens may be the most likely to cause deleterious cytoplasmic problems among Entamoeba congeners.…”
mentioning
confidence: 99%
“…Moreover, all of them were newly identified and unique to Indian isolates. Since SREHP is an immunogenic surface antigen, such high degree of genetic diversity could be due to the host selection pressure on parasite during immune evasion (Das and Ganguly, 2014). Distribution of repeat patterns among disease groups has also revealed an interesting scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In examining their sequenced genomes Weedall et al observed substantial copy number variation in E. histolytica strains and repeat elements at the border of the duplicated DNA [18]. It is therefore feasible to speculate that the abundant repeat elements may play a role in promoting the expansion of the different paralogous gene families that occur in E. histolytica isolates [18,29]. This expansion in gene families provide an additional means of increasing gene diversity by permitting recombination between the paralogous gene copies as is postulated to have been increased the diversity in the gene families encoding the intermediate and light subunits of the Galactose and N-acetyl-D-galactosamine inhibitable lectin [30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that they are a confounding factor for the common microscopic method of diagnostics in Bangaldesh E. dispar and E. bangladeshi have also been the subject of additional study [4246]. At the time of writing the genome of E. bangladeshi has not been sequenced however preliminary evidence suggests that that all four species have a high degree of homology [7,18,29,47]. Despite this similarity it has long been known that significant differences exist between the species and it has been hypothesized that these may result in the disparity observed in their potential virulence [18,20,48,49].…”
Section: Introductionmentioning
confidence: 99%